ANALISIS PENGARUH IKLIM SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DAN KEDISIPLINAN SISWA - Rezky Dwika Dana Putri; Syamsu A Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the influence of school climate on student learning motivation and student discipline. Quality education relies heavily on an effective learning process, which is supported by students' internal factors: motivation and discipline. A strong external factor presumed to influence these variables is the school climate, defined as the perceived quality and psychological characteristics of the school environment by its members. This study uses a descriptive qualitative method with a library research technique. Data were collected from various secondary sources such as books, journals, and previous research, and then analyzed descriptively. The results of the literature review indicate that school climate has a positive and significant influence on both learning motivation and student discipline. A positive school climate characterized by supportive relationships, safety, orderliness, and adequate facilities serves as a strong external stimulus to increase students' internal drive (motivation) to learn. Furthermore, a school climate that is orderly, democratic, and implements norms and rules fairly and consistently is proven effective in shaping and enhancing student discipline. Keywords: School Climate, Learning Motivation, Student Discipline